Managing Risk and Creating Value with Microfinance - Goldberg, Mike; Palladini, Eric (World Bank, 2012)
This report brings together the results of an eight-part series of presentations by leading experts in issues directly related to microfinance institutional sustainability. It is intended for microfinance institution (MFI) board members, managers, and staff members as well as for government regulators, supervisors, and donor staff members. The first four chapters include topics in risk management: (1) risk management systems, (2) good governance, (3) interest rates, and (4) micro-insurance. The last four chapters include four topics in new product development and efficient delivery methodologies: (5) housing microfinance, (6) micro-leasing, (7) disaster preparedness products and systems, and (8) new technologies. The objectives of the series were as follows: i) to strengthen MFIs by disseminating innovative approaches in risk management, cost control, governance, and new technologies; ii) to promote a South-South exchange of experiences and lessons learned; iii) to promote greater ties among the MFIs in the region and between MFIs and government supervisors and regulators; and iv) to highlight the Bank's ability to mobilize international technical expertise in microfinance.